2010
DOI: 10.1186/ar3064
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases interleukin-10 levels both intraarticularly and peri-synovially in patients with knee osteoarthritis: a randomized controlled trial

Abstract: IntroductionThe microdialysis method was applied to the human knee joint with osteoarthritis (OA) in order to reveal changes in biochemical markers of cartilage and inflammation, intraarticularly and in the synovium, in response to a single bout of mechanical joint loading.MethodsThirty-one female subjects with OA of the knee were randomized to non-exercise (NEx) or exercise (Ex) groups. Following acute resistance exercise (25 sets of 10 repetitions at 60% of 1 Repetition Maximum) or none (NEx), peripheral ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 41 publications
2
138
0
6
Order By: Relevance
“…IL-4 possesses anti-inflammatory properties, underlined by the enhancement of the breakdown of mRNA for the transcription factor of nuclear factor kappa B (NFκB) and the suppression of both IL-1 and tumor necrosis factor alpha (TNF-α) expression [16]. IL-1 and TNF-α reduction is due to IL-10 which suppresses the translocation of NFκB, working in addition to IL-4 [17]. Moreover, the IL-10 expression has been found enhanced following a single bout of resistance exercise in patients with OA, and this has been included among the beneficial effects of exercise on OA [18].…”
Section: Cell Signaling and Articular Cartilage Morphology Changes Inmentioning
confidence: 99%
“…IL-4 possesses anti-inflammatory properties, underlined by the enhancement of the breakdown of mRNA for the transcription factor of nuclear factor kappa B (NFκB) and the suppression of both IL-1 and tumor necrosis factor alpha (TNF-α) expression [16]. IL-1 and TNF-α reduction is due to IL-10 which suppresses the translocation of NFκB, working in addition to IL-4 [17]. Moreover, the IL-10 expression has been found enhanced following a single bout of resistance exercise in patients with OA, and this has been included among the beneficial effects of exercise on OA [18].…”
Section: Cell Signaling and Articular Cartilage Morphology Changes Inmentioning
confidence: 99%
“…Following acute resistance exercise, a significant increase in IL-10 was observed in the intra-articular and synovial spaces of subjects who exercised when compared to a nonexercise group (Helmark et al 2010). Increases in IL-10 expression were also reported in chondrocytes in antigen-induced arthritis, an animal model of rheumatoid arthritis, after two weeks of continuous passive motion when compared to immobilized joints (Ferretti et al 2005;Ferretti et al 2006).…”
Section: Local Effects On Cartilagementioning
confidence: 83%
“…group was found. The important role of IL-10 in natural inhibition of arthritis had been reported [26].Guo et al reported better effect of US compared to laser on knee OA of rabbits [27]. In contrast to us, Alves et al reported decreased expression of not only IL-1 beta but also IL-6 and TNFalpha by using 50 mW laser therapy and higher reduction of TNF alpha with 100 mW in joint inflammation induced by papain [12].…”
Section: Effects Of Ultrasound Versus Low Level Laser Therapy In Levomentioning
confidence: 85%